Initiation and dose optimization for levodopa-carbidopa intestinal gel: Insights from phase 3 clinical trials - Lew, Mark F.; Slevin, John T.; Krüger, Rejko; Martínez Castrillo, Juan Carlos; Chatamra, Krai; Dubow, Jordan S.; Robieson, Weining Z.; Benesh, Janet A.; Fung, Victor S.C. (Parkinsonism & related disorders, 2015)
Levodopa-carbidopa intestinal gel (LCIG) provides continuous infusion and reduces “off” time in advanced Parkinson's disease (PD) patients with motor fluctuations despite optimized pharmacotherapy. Clinical experience with 2 LCIG dosing paradigms from phase 3 studies was examined. In an open-label, 54-week study, LCIG was initiated as daytime monotherapy via nasojejunal (NJ) tube then switched to percutaneous endoscopic gastrojejunostomy (PEG-J) tube; adjunctive therapy was permitted 28 days postPEG-J. In a 12-week, double-blind, placebo-controlled, double-dummy trial, patients continued stable doses of existing anti-PD medications, but LCIG replaced daytime oral levodopa-carbidopa and was initiated directly via PEG-J. In the open-label study, 92% of 354 patients received monotherapy at post–PEG-J week 4; mean titration duration was 7.6 days; dosing remained stable post-titration (mean total daily dose [TDD] was 1572 mg at last visit). In the double-blind trial, 84% received polypharmacy; mean titration took 7.1 days for the LCIG arm (TDD post-titration: 1181 mg; n = 37). At post–PEG-J week 4, mean “off” time with LCIG was reduced by 3.9 h (open-label/monotherapy study) and 3.7 h (double-blind/polypharmacy trial). NJ treatment (open-label study only) required an additional procedure with related adverse events (AEs) and withdrawals. The most common AEs during PEG-J weeks 1–4 in the open-label/monotherapy and double-blind/polypharmacy trials, respectively, were complication of device insertion (35%, 57%) and abdominal pain (26%, 51%). Discontinuations due to nonprocedure/nondevice AEs were low (2.2%, 2.7%). These results support the option of initiating LCIG with or without NJ and as either monotherapy or polypharmacy. •LCIG can be initiated directly via PEG-J; consider temporary NJ in select patients.•In advanced PD, LCIG is effective as monotherapy or as part of existing polytherapy.•Dose optimization with LCIG can be achieved within days.•Once titrated, LCIG dosage remained stable during a study of more than a year.•Discontinuations due to nonprocedure/nondevice AEs were low (<3%).